2002
DOI: 10.1046/j.1469-1809.2002.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability in Poles and Russians

Abstract: Mitochondrial DNA (mtDNA) sequence variation was examined in Poles (from the PomeraniaKujawy region ; n l 436) and Russians (from three different regions of the European part of Russia ; n l 201), for which the two hypervariable segments (HVS I and HVS II) and haplogroup-specific coding region sites were analyzed. The use of mtDNA coding region RFLP analysis made it possible to distinguish parallel mutations that occurred at particular sites in the HVS I and II regions during mtDNA evolution. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
117
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 30 publications
17
117
3
Order By: Relevance
“…A set of 7245 HVS1 sequences was analysed between sites 16090-16365 (276 base-pairs). In addition to sequences analysed in Helgason et al (2000aHelgason et al ( , 2001, the following are added: 50 Germans (Baasner et al 1998), 106 Sicilians (Cali et al 2001), 118 Spanish (Crespillo et al 2001), 154 Swiss (DimoSimonin et al 2000, 300 Yugoslavian (see Table 2), 20 Finns and 10 Polish (Jorde et al 2000), 50 Russians, (Malyarchuk & Derenko, 2001), 436 Poles and 201 Russians (Malyarchuk et al 2002), 129 Slovakians (E. Metspalu, T. Kivisild, K. Kaldma, M. Reidla & R. Villems, GenBank accession numbers AJ240164-AJ240292), 74 Norwegians (Passarino et al 2002), 241 Portuguese (Pereira et al 2000), 300 Canary Islanders (Rando et al 1999), 83 Italians (Tagliabracci et al 2001) and 186 Cretans (R. Villems, GenBank accession numbers AJ274757-AJ274942). Sequences that did not completely span the regions defined above were omitted from analysis, and population samples analysed in Helgason et al (2000a) with sample sizes below 70 were excluded.…”
Section: Genetic Systems and Population Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of 7245 HVS1 sequences was analysed between sites 16090-16365 (276 base-pairs). In addition to sequences analysed in Helgason et al (2000aHelgason et al ( , 2001, the following are added: 50 Germans (Baasner et al 1998), 106 Sicilians (Cali et al 2001), 118 Spanish (Crespillo et al 2001), 154 Swiss (DimoSimonin et al 2000, 300 Yugoslavian (see Table 2), 20 Finns and 10 Polish (Jorde et al 2000), 50 Russians, (Malyarchuk & Derenko, 2001), 436 Poles and 201 Russians (Malyarchuk et al 2002), 129 Slovakians (E. Metspalu, T. Kivisild, K. Kaldma, M. Reidla & R. Villems, GenBank accession numbers AJ240164-AJ240292), 74 Norwegians (Passarino et al 2002), 241 Portuguese (Pereira et al 2000), 300 Canary Islanders (Rando et al 1999), 83 Italians (Tagliabracci et al 2001) and 186 Cretans (R. Villems, GenBank accession numbers AJ274757-AJ274942). Sequences that did not completely span the regions defined above were omitted from analysis, and population samples analysed in Helgason et al (2000a) with sample sizes below 70 were excluded.…”
Section: Genetic Systems and Population Samplesmentioning
confidence: 99%
“…These sequences represent all European population samples we could locate for the specified regions. In addition to sequences analysed in Helgason et al (2000aHelgason et al ( , 2001, data from the following sources are incorporated: 254 Yugoslavians (M. Harvey, K. Gordon, K. Owens, M. Lee & M.-C. King, GenBank accession numbers AY005495-AY005795), 199 Russians and 436 Poles (Malyarchuk et al 2002), 118 Spanish (Crespillo et al 2001), 241 Portuguese (Pereira et al 2000), 83 Italians (Tagliabracci et al 2001 Abbreviations in column titles are N = sample size, k = number of distinct haplotypes and S = number of polymorphic sites. MPD = mean pairwise differences between all pairs of sequences.…”
Section: Genetic Systems and Population Samplesmentioning
confidence: 99%
“…Hypervariable segments I and II (HVS I and II) of the mtDNA noncoding control region (CR) were amplified and sequenced as described elsewhere (Malyarchuk et al 2002). The nucleotide sequences of HVS I from position 15999 to 16400 and HVS II from position 30 to 407 were determined and compared with the Cambridge reference sequence (CRS: Anderson et al 1981;Andrews et al 1999).…”
Section: Mtdna Analysismentioning
confidence: 99%
“…Using an unplanned test, we found that haplogroups K and H made the largest contribution to the observed overall heterogeneity (Table 1). Accordingly, a close examination of the data (Table 1) revealed that the frequency of haplogroup K in the RU sample was Numbers for the non-Jewish populations are taken from Malyarchuk et al 10 To avoid small sample size, haplogroups were either grouped based on phylogeny (ie, N1 and I, W and X) or added to 'others' (haplogroups L, M and Pre-HV). considerably lower than that in the other two populations; similarly, the frequency of haplogroup H was lower in the Polish group.…”
mentioning
confidence: 99%
“…However, these researchers considered Ashkenazi Jews as a single entity, assuming that all Ashkenazi Jewish communities from Central and Eastern Europe originated exclusively from the Rhine basin and thus compared Ashkenazi Jewish mtDNA diversity only with that of non-Jewish Germans. To test for possible admixture between Ashkenazi communities and local non-Jewish populations, we used a log-linear model 8 to compare mtDNA haplogroup distribution of the Jewish RU and Polish groups to the available data on the haplogroup distribution of nonJewish RU and Polish populations, respectively 10 (Table 2). This analysis revealed a significant divergence in total haplogroup distribution between the Ashkenazi Jewish and the local populations (ethnic background  haplogroup interaction term, G ¼ 173, df ¼ 8, Po0.001).…”
mentioning
confidence: 99%